2016
DOI: 10.1155/2016/9821767
|View full text |Cite
|
Sign up to set email alerts
|

Anticerebral Ischemia-Reperfusion Injury Activity of Synthesized Puerarin Derivatives

Abstract: When cerebral ischemia-reperfusion injury happened in patients, multiple pathological processes occur, such as leukocyte infiltration, platelet, and complement activation, which would result in cognitive dysfunction and inflammation. Puerarin has shown protective effect on injury of neural cell. In order to enhance this protective effect of puerarin, puerarin derivatives with different log⁡P values were designed and synthesized. The original phenolic hydroxyl in the puerarin molecules was substituted in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The prevalence of aspirin nonresponse was 27.5% in present study, and was similar to the prevalence reported in our previous studies [ 8 , 11 , 21 ] and some other studies [ 9 , 22 ]. A recent systematic review and meta-analysis showed that the prevalence of high on-treatment of platelet reactivity (HTPR) on aspirin was 23% (95% CI: 20–28%), and the patients with HTPR had a significantly higher risk for ischemic stroke recurrence (relative risk = 1.81, 95% CI: 1.30–2.52; P < 0.001) [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of aspirin nonresponse was 27.5% in present study, and was similar to the prevalence reported in our previous studies [ 8 , 11 , 21 ] and some other studies [ 9 , 22 ]. A recent systematic review and meta-analysis showed that the prevalence of high on-treatment of platelet reactivity (HTPR) on aspirin was 23% (95% CI: 20–28%), and the patients with HTPR had a significantly higher risk for ischemic stroke recurrence (relative risk = 1.81, 95% CI: 1.30–2.52; P < 0.001) [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The finding is consistent with our present study. The mechanisms associated with aspirin nonresponse are complex and mutilfactorial, such as noncompliance, diabetes mellitus, reduced absorption, the biosynthesis of thromboxane A2 from pathways not inhibited by aspirin as well as alternative pathways involved in platelet activation not blocked by aspirin [ 9 , 11 , 21 , 22 ]. In present study, our results also showed that the diabetes mellitus was associated with aspirin nonresponse.…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin–one of the active ingredients in herbal medicine–has protective functions in multiple tissues, such as bone, liver, the cardiovascular system and the brain [ 6 ]. Studies have demonstrated that in rats with cerebral I/R injury, puerarin enhanced antioxidant capacity, removed lipid peroxidation products, improved antioxidant activity, and reduced the degree of focal ischemic injury [ 22 ]. Here we demonstrated that puerarin-pretreatment improves behaviors in I/R rats, as observed the MWM test, thereby suggesting that puerarin benefits the recovery of hippocampus-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It was resulted in an enhancement of protective activity against cerebral ischemic damage in a mouse model of ischemia/reperfusion-evoked dementia. Specifically, these two derivatives showed stronger suppression of inflammation (iNOS activity) and elevation of brain cortex Ca 2+ -Mg 2+ -ATPase activity ( Ji et al, 2016b ). Puerarin-7- O -glucuronide ( Figure 4J ), a water-soluble metabolite of puerarin, lessened intracellular superoxide level and improved total SOD activity, glutathione/glutathione disulfide ratio and total anti-oxidant capacity in xanthine oxidase/xanthine-induced neonatal rat cardiomyocytes.…”
Section: The Derivatives and Drug Deliery Systems Of Puerarinmentioning
confidence: 99%